Deprotonation of a dinuclear copper complex of 3, 5-diamino-1, 2, 4-triazole for high oxygen reduction activity. Issue 14 (11th March 2015) - Kato, Masaru; Kimijima, Ken'ichi; Shibata, Mari; Notsu, Hideo; Ogino, Kazuya; Inokuma, Kiyoshi; Ohta, Narumi; Uehara, Hiromitsu; Uemura, Yohei; Oyaizu, Nobuhisa; Ohba, Tadashi; Takakusagi, Satoru; et al.
Abstract : In situ XAFS studies of a copper catalyst revealed its coordination geometrical changes caused by deprotonation. Abstract : A dinuclear copper(ii ) complex of 3, 5-diamino-1, 2, 4-triazole is one of the highly active copper-based catalysts for the oxygen reduction reaction (ORR) in basic solutions. Our in situ X-ray absorption near edge structure measurements revealed that deprotonation of the triazole ligand might cause coordination geometrical changes, resulting in the enhancement of the ORR activity.